Perancangan Sistem Order Material pada Supporting Department PT XYZ dengan Metode System Development Life Cycle - Yulianto, Marcelino Alexander; Hadi, Yuswono; Noya, Sunday (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2023)
The study focuses on the Supporting department, responsible for producing components for assembling minibuses, including the J type. The department faces several issues, including a 60% confusion rate in component names out of the 600 components, delays and errors in component delivery spanning 4 to 16 hours, and the absence of a Standard Operating Procedure (SOP). Addressing these challenges necessitates the development of a material order system, tackled using the System Development Life Cycle (SDLC). Through SDLC analysis, solutions were derived, involving the creation of system programs, enhancing system flow, standardizing component names, grouping components into kits, establishing component catalogs, and formulating SOPs. This comprehensive solution was implemented at PTXYZ. The outcomes revealed significant improvements: standardization of component names among operators, administrators, and Microsoft GP, where 600 raw components were grouped into 98 packages, reducing delays to less than one working hour, meeting production schedules without delivery errors, and successful implementation of SOPs and catalogs facilitating the production process. Continuous monitoring is crucial to prevent the recurrence of delivery delays and name confusion.